MOTHERS’ PERCEIVED HEALTH WORKER INFORMATION AND COMMUNICATION TECHNOLOGY USE AND DISSEMINATED INFORMATION ON MATERNAL HEALTH PRACTICES IN NIGERIA (2017)
High maternal and child mortality rates have been linked to unhealthy practices by mothers in Nigeria. These practices could be traced to obsolete and inadequate information available to mothers. There are several e-health interventions by organisations to enhance Maternal Health Practices (MHP) with little consideration for mothers’ perception of health worker Information and Communication Technology (ICT) use and relevance of disseminated information to MHP. This study, therefore, examined mothers’ perceived health worker ICT use and the relevance of disseminated information to MHP in Nigeria. Venkatesh’s Unified Theory of Acceptance and Use of Technology provided the framework, while descriptive survey design was adopted. Nine public health facilities in Ondo (4), Imo (1), Kaduna (2) and Gombe (2) States with on-going e-health projects were purposively selected. Total enumeration technique was employed to select 931 mothers who were attending antenatal and postnatal clinics. Instruments used were Mothers’ perceived health worker ICT use (α=0.79), Mothers’ perception of disseminated information relevance (α =0.86) and MHP (α=0.81) scales. Quantitative data were complemented with four sessions of focus-group discussion with mothers in Ondo (10 participants), Imo (8 participants), Kaduna (6 participants) and Gombe (6 participants) States and key informant interviews with nine health workers in-charge of the e-health projects. Data were collection from February to September 2015. Descriptive statistics, Pearson’s Product moment correlation and Multiple regression were used to analyse quantitative data at 0.05 level of significance, while qualitative data were content analysed. Majority of the mothers were married (95.9%) and their mean age was 30 ±8 years. Maternal health information (MHI) was disseminated through mobile phones (76.0%), radio (66.9%), television (55.1%), public address system/projector (27.3%) and the Internet (2.4%). The MHI themes were on: appointment reminders (45.0%), emotional changes (39.5%), family planning (34.0%), nutrition (32.8%), medication in pregnancy (30.6%) and breastfeeding (26.0%). About 96.0% of the mothers agreed that disseminated information were relevant. Mothers’ perceived health workers’ ICT use (r = 0.26) and disseminated information relevance (r = 0.31) had significant relationship with MHP of mothers. There was a significant joint contribution of mothers’ perceived health workers’ ICT use and disseminated information relevance on MHP (F (2; 928) = 60.87, R = 0.34, Adj. R2 =0.11), accounting for 11.4% of its variance. Mothers’ perceived disseminated information relevance (β = 0.32) and health workers’ ICT use (β = 0.13) contributed to MHP. Unstable power supply and internet data cost are factors inhibiting effective use of ICT. Mothers stated that the disseminated information improved their MHP. Health workers’ effective use of information and communication technology and mothers’ positive perception of disseminated information improved maternal health practices in public health facilities in Nigeria. Therefore, future e-health project should take cognizance of mothers’ perception of health worker information and communication technology use and relevance of disseminated information to improve maternal health practices. Health policies should target Internet data subsidy for pregnant and nursing mothers to increase their access to e-health information.